The Red Dean of Canterbury: the public and private faces of Hewlett Johnson - Butler, John R. (Scala, 2011)
"In the mid-twentieth century, few people in Britain divided public opinion more than Hewlett Johnson. To the high-profile Dean of Canterbury Cathedral, the principles of communism were all but indistinguishable from Christian teaching about the Kingdom of God on earth, and he used his position to promote his beliefs. A global campaigner for peace in the Cold War era, he had audiences with Gandhi, Stalin, Khrushchev, Tito, Mao Tse-Tung and Chou En-Lai, Fidel Castro and Che Guevara. Wherever he spoke and preached, he was either adored as a Christian visionary or hated as a mouthpiece of Soviet propaganda. In his timely new biography, drawing for the first time on Johnson's own personal papers and other previously unexplored archives, including those of M15, John Butler explores the charismatic and intriguing figure of the 'Red Dean'"--Publisher's description, p. [4] of dust jacket